Penerapan Terapi Kelompok Teknik Self disclosure untuk Meningkatkan Penyesuaian Diri Anak Jalanan Di Panti Sosial - Riani, Widia Sesha; Putri, Roza Elmanika; Sovitriana, Rilla (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The Bina Insan Bangun Daya 2 Jakarta Social Institution is a social institution that providestemporary shelter for people with Social Welfare Problems (PMKS) as a result of policing and socialoutreach and has the responsibility to provide motivation and social guidance for PMKS who willbe referred to related social institutions in accordance with the problem, either being returned tothe family or sent back to the place of origin. One of the PMKS in the community is street children;they are given guidance and provided with services and rehabilitation so that they can adjust to thecommunity environment and have the ability to start new businesses and no longer associateillegally and work on the streets; it's just that street children who are in Social Institutions. Aftercarrying out a psychological examination with clinical interviews, observation, psychological tests,and self-adjustment scales, it is known that WBS are less able to adapt, which is marked by beinglazy to follow various guidance and skills training, preferring to be alone, being unable to acceptoneself, and being lazy to get along. After doing group therapy with self-disclosure techniques, streetchildren begin to want to participate in activities, are calm and optimistic, and are able to socialise.The percentage increase in self-esteem averaged 27.9%.